Quantitative comparison and rapid discrimination of Panax notoginseng powder and Caulis clematidis armandii using NMR combined with pattern recognition. (21st October 2022) - Chen, Honghai; Ding, Zenan; Dai, Tao; Lin, Jianzhong; Xu, Dunming; Xia, Feng; Feng, Jianghua; Shen, Guiping
Abstract: BACKGROUND: The market demand for Panax notoginseng ( P. notoginseng ) is growing rapidly because of its useful properties in food and medicine. However, the frequent adulteration of P. notoginseng seriously affects the health of consumers and is a great challenge to food safety. In this study, low‐ and high‐field nuclear magnetic resonance (LF/HF‐NMR) were applied to detect the transverse relaxation distribution of P. notoginseng contaminated with different ratios of Caulis clematidis armandii ( CCA ) and the components in P. notoginseng and CCA, respectively. RESULTS: Fifty‐seven kinds of major and minor components in P. notoginseng and CCA were identified and quantified from their high‐resolution NMR spectra, and there were significant differences in ginsenosides, sucrose, and glucose between P. notoginseng and CCA . Furthermore, the partial least squares regression analysis results indicated that LF‐NMR parameters ( T 21 and S 21 ) changed linearly as the ratio of CCA increased, and these changes were attributed to the variations in polysaccharide and sucrose in adulterated P. notoginseng . CONCLUSION: In the relaxation time‐based pattern recognition models, the authentic P. notoginseng powder could be classified with 100% accuracy from adulterated P. notoginseng when the adulteration ratio was greater than 30%, demonstrating the possibility of LF‐NMR, in combination with pattern recognition, for rapid discrimination of food authenticity. © 2022 Society of Chemical Industry.